LOV‐domain photoreceptor, encoded in a genomic island, attenuates the virulence of Pseudomonas syringae in light‐exposed Arabidopsis leaves - Moriconi, Victoria (2013)
In Arabidopsis thaliana, light signals modulate the defences against bacteria. Here we show that light perceived by the LOV domain‐regulated two‐component system (Pst–Lov) of Pseudomonas syringae pv. tomato DC3000 (Pst DC3000) modulates virulence against A. thaliana. Bioinformatic analysis and the existence of an episomal circular intermediate indicate that the locus encoding Pst–Lov is present in an active genomic island acquired by horizontal transfer. Strains mutated at Pst–Lov showed enhanced growth on minimal medium and in leaves of A. thaliana exposed to light, but not in leaves incubated in darkness or buried in the soil. Pst–Lov repressed the expression of principal and alternative sigma factor genes and their downstream targets linked to bacterial growth, virulence and quorum sensing, in a strictly light‐dependent manner. We propose that the function of Pst–Lov is to distinguish between soil (dark) and leaf (light) environments, attenuating the damage caused to host tissues while releasing growth out of the host. Therefore, in addition to its direct actions via photosynthesis and plant sensory receptors, light may affect plants indirectly via the sensory receptors of bacterial pathogens.